Semantic Knowledge Representation for Strategic Interactions in Dynamic Situations - Calvo Tapia, Carlos; Villacorta-Atienza, José Antonio; Díez-Hermano, Sergio; Khoruzhko, Maxim; Lobov, Sergey; Potapov, Ivan; Sánchez-Jiménez, Abel; Makarov, Valeri A. (Frontiers in Neurorobotics, 2020)
Evolved living beings can anticipate the consequences of their actions in complex multilevel dynamic situations. This ability relies on abstracting the meaning of an action. The underlying brain mechanisms of such semantic processing of information are poorly understood. Here we show how our novel concept, known as time compaction, provides a natural way of representing semantic knowledge of actions in time-changing situations. As a testbed, we model a fencing scenario with a subject deciding between attack and defense strategies. The semantic content of each action in terms of lethality, versatility, and imminence is then structured as a spatial (static) map representing a particular fencing (dynamic) situation. The model allows deploying a variety of cognitive strategies in a fast and reliable way. We validate the approach in virtual reality and by using a real humanoid robot.